DESIGNING A BLOCKCHAIN-ENABLED SINGLE WINDOW (BESW) MODEL FOR SECURE AND TRANSPARENT CUSTOMS DATA EXCHANGE - KHOLIQ ABDULLAH (Unit Penerbitan Politeknik Keuangan Negara STAN, 2025)
This paper proposes a conceptual framework called the Blockchain-Enabled Single Window (BESW) to enhance the security, transparency, and interoperability of customs data exchange, particularly in the Delivery Order (DO) and Surat Penyerahan Petikemas (SP2) process. The model introduces four integrated layers: (1) an Infrastructure Layer using a permissioned blockchain network to connect customs, port, banking, and logistics stakeholders; (2) a Data and Smart Contract Layer for automated document validation and payment verification; (3) an Interoperability Layer harmonized with WCO Data Model 3.11, UN/CEFACT, and ISO 20022; and (4) an Application and Audit Layer offering real-time monitoring and immutable audit logs. BESW aims to complement Indonesia’s National Single Window (INSW) and ASEAN Single Window (ASW) by establishing a distributed trust architecture that enhances efficiency and institutional accountability. The paper concludes by outlining future empirical validation to assess feasibility, governance adaptation, and scalability for ASEAN-wide customs digitalization.